Trump's and Clinton's Style and Rhetoric during the 2016 Presidential Election. Issue 2 (3rd April 2018) - Savoy, Jacques
Abstract: The present paper examines the style and rhetoric of the two main candidates (Hillary Clinton and Donald Trump) during the 2016 presidential election. Based on interviews and TV debates, the most frequent lemmas indicate an emphasis on the pronoun I for both candidates while in speeches, the pronoun we appears more frequently. According to overall stylistic indicators, Trump adopts a simple and direct communication style, preferring short sentences, avoiding complex formulations and employing a reduced vocabulary. In the oral form, Trump frequently uses verb phrases (verbs and adverbs) and pronouns while Clinton is more descriptive (more nouns and prepositions). As expected, the speeches present differences from the oral form. For Trump, the difference is clearly larger, distinctively depicting two communication styles (oral and written). The specific terms or sentences associated with each candidate reveal their characteristic topics and style, such as the repetition of expressions and negativity for Trump. Based on predefined word lists, this study indicates that Clinton's rhetoric employs more cognitive words, while negative emotions and exclusive terms occur more frequently in Trump's verbiage.